Konsensus Perhimpunan Dokter Spesialis Bedah Digestif Indonesia tentang Pedoman Diagnosis dan Tatalaksana Batu Saluran Empedu - Muhammad Iqbal Rivai; Arnetta Naomi Louise Lalisang; Adianto Nugroho; Agung Ary Wibowo; Adeodatus Yuda Handaya; Fransiscus Arifin; Indah Situmorang; Erik Prabowo; Irwan Irwan; Maria Mayasari; Michael Tendean; Reno Rudiman; Kunsemedi Setyadi; Muhammad Shobachun Niam; Bambang Suprapto; Jeffri Putra; Tommy Lesmana; Yarman Mazni; Adi Muradi Muhar; I Made Mulyawan; Warsinggih Warsinggih; Toar Jean Maurice Lalisang (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2024)
Introduction: Choledocholithiasis, the presence of stones in the common bile duct (CBD), is a challenge in the field of digestive surgery due to the wide range of cases with varying levels of difficulty. Until now, the options for diagnostic and therapeutic modalities have been increasingly evolving, ranging from non-invasive to invasive procedures. Therefore, the Indonesian Society of Digestive Surgeons provides recommendations for the management of CBD stone cases in Indonesia.Method: The consensus was developed using the Delphi survey method involving digestive surgery experts from various cities in Indonesia. Several issues related to the diagnosis and management of CBD stones were formulated and answered based on current research, while also considering the opinions of the experts.Result: This consensus consists of two parts: 15 recommendations related to the selection of diagnostic modalities and 10 recommendations related to management options. Recommendations regarding diagnosis include the use of ultrasonography, abdominal CT-scan, and magnetic resonance cholangiopancreatography (MRCP). In addition to standard therapeutic procedures, this consensus also provides recommendations regarding contemporary procedures such as endoscopic retrograde cholangiopancreatography (ERCP), laparoscopic common bile duct exploration (LCBDE), and open common bile duct exploration (OCBDE).Conclusion: These recommendations are aimed to assist digestive surgery experts in providing the best management for CBD stone cases.